Ten weeks of 100% orange juice consumption had a marginal effect on women's skin health compared to a low-flavanone orange-flavored control beverage: a pilot randomized trial - Fu, Wenyi; Gu, Liwei (Frontiers in Nutrition, 2025)
Human skin health deteriorates after age 40, particularly due to ultraviolet (UV) radiation, a major extrinsic factor contributing to photoaging. This study investigated whether daily consumption of 100% orange juice could reduce UVB-induced erythema, improve skin health, and lower biomarkers of oxidative stress and inflammation. A randomized, single-blinded, crossover trial was conducted in 24 healthy women aged 40–65. Participants consumed 12 oz of 100% orange juice or an orange-flavored control beverage daily for 10 weeks, followed by a 28-day washout before switching beverages for another 10 weeks. Skin assessments and blood sample collection were conducted at baseline, week 5, and week 10. Orange juice offers significantly higher daily flavanone content (81.46 mg/day) than the control beverage (29.60 mg/day). Ten weeks of orange juice consumption significantly reduced forearm wrinkles and showed a trend toward reduced skin roughness. However, no significant improvements were observed in UVB-induced erythema and other skin health parameters, including transepidermal water loss, skin hydration, or elasticity. Furthermore, blood levels of matrix metalloproteinase-9, advanced glycation end products, superoxide dismutase, glutathione peroxidase, IL-6, TNF-α, and high-sensitivity C-reactive protein remained unchanged. In conclusion, daily consumption of orange juice for 10 weeks had a marginal effect on skin health.